Analisis Rasio Keuangan Terhadap Harga Saham Pada Perusahaan Farmasi - Viola Syukrina E Janrosl; Handra Tipa (Politeknik Ganesha Medan, 2022)
The research has the objective of analyzing financial ratios to stock prices of pharmaceutical sector companies that are listed on the Indonesia Stock Exchange. Accumulated buy events often occur in pharmaceutical company shares, but the issuer's share price remains stagnant. Where shares are bought by many investors, but the price is still maintained. This research was conducted on the Indonesia Stock Exchange of pharmaceutical entities on the IDX. The population in this research is the financial statements of pharmaceutical entities on the IDX for the period 2016-2020 and that meet the sample criteria, there are 10 companies. This research applies financial ratios including the current ratio, debt to equity ratio. The method applied is a multiple regression linear analysis model. The findings of the F test simultaneously current ratio and debt equity ratio have a significant effect on stock prices. The findings of the current ratio t test have a significant impact on stock prices. debt equity ratio has no significant effect on stock prices. Based on the value of R Square 0.180. This figure is 18% of the percentage of variables studied in this research, the remaining 82% is due to other factors that have not been discussed in the research